EMPOWERING COMMUNITIES THROUGH ISLAMIC BUSINESS PRACTICES: A CASE STUDY OF BPRS AL-MA’SOEM - Barkah, Muhammad Caesario (Branding: Jurnal Manajemen dan Bisnis, 2024)
This study addresses the problem of balancing profitability with social responsibility within Islamic finance institutions, specifically focusing on how BPRS Al-Ma’soem empowers local communities through Islamic business practices and Corporate Social Responsibility (CSR) initiatives. The primary objective of this research is to explore the impact of BPRS Al-Ma’soem’s Islamic financial practices and CSR activities on community welfare and economic resilience in West Java, Indonesia. Using a qualitative case study approach, the study examines BPRS Al-Ma’soem’s financial performance and CSR initiatives from 2019 to 2023. Data was gathered from secondary sources, including financial and CSR reports, to analyze key metrics such as asset growth, profit, and allocation of CSR funds. Findings reveal that BPRS Al-Ma’soem has achieved steady financial growth, which has enabled the bank to support various community initiatives in education, healthcare, and infrastructure. The CSR programs, funded through Qardhul Hassan and Zakat, Infaq, and Sadaqah (ZIS), have contributed significantly to local socioeconomic resilience. This research highlights BPRS Al-Ma’soem’s success in balancing profitability with social impact, offering insights for other Islamic financial institutions aiming to enhance community welfare while maintaining financial stability.